Hygiene and Sanitation Factors Affecting Contamination of Soil-Transmitted Helminths in Household Water Sources in Jember, Indonesia - Epafroditus Sanjaya Adiguna; Wiwien Sugih Utami; Ika Rahmawati Sutejo; Bagus Hermansyah; Yunita Armiyanti (Althea Medical Journal, 2022)
Background: Water sources used by households are at risk of contamination by soil-transmitted helminths (STH). Hygiene and sanitation have an essential role in the transmission and contamination of STH. The objective of this study was to analyze whether there was an association between hygiene and sanitation factors with STH contamination in household water sources in Jember Regency, East Java Province, Indonesia.Methods: This cross-sectional analytic study was carried out from December 2020 to March 2021, including 46 samples from 23 respondents in Sukowono District and 23 respondents in Sukorambi District, Jember Regency, selected using a purposive sampling technique. Primary data on hygiene and sanitation risk factors were obtained from questionnaire interviews. The STH contamination in household water sources was examined by sedimentation and flotation methods. Data were analyzed using Fisher Exact test.Results: The identification of STH contamination in household water sources using microscope examination found hookworm species contaminated 8.7% (n=4) of water sources. There was a significant association between the type of human sewage disposal with STH contamination in household water sources (p=0.037). There was no association between hygiene and other sanitation factors with STH contamination in household water sources (p>0.05).Conclusions: Human sewage disposal that goes directly to sewers and rivers can cause contamination of water sources by STH. Therefore, it is important to dispose of human waste in septic tanks that comply with health requirements to prevent the transmission of STH to humans through water sources.